Hebrew Prophecy and the Foundations of Political Opposition - Maddox, Graham (Australian religion studies review, 2008)
Political opposition, as institutionally provided for in the constitutional set-up of a democratic polity, implies pluralism, toleration and the guarantee of limited and contested government. Its modern roots can be traced to the era of puritan resistance to the English Crown in the seventeenth century and its theoretical justification in the Country Ideology of the seventeenth century. In that movement theorists liberally resorted to ancient Roman argument and to the example of the Hebrew prophets. Some modern studies of opposition attribute its origins to the Roman tribunate, which Rousseau inaccurately claimed was established to contain executive power without seeking any for itself. This characterization is better suited to the received tradition about the Hebrew prophets.